A case against plastics ; Search for Amanda ; swimming babies [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Tackles non-biodegradable waste flowing into the shores of Bataan. A newly born baby in a private hospital disappeared without a trace before she was to go home with her parents. The Lozada School of Swimming teaches babies less than a year old to swim.
A case against plastics (13 min.) -- Search for Amanda (19 min.) -- Swimming babies (9 min.)
VHS
Keywords: Rodena, Amanda Danielle. Kidnapping; Baguio Medical Center; Water -- Pollution -- Philippines -- Bataan; Bataan care -- Philippines -- Baguio City; Kidnapping -- Philippines -- Baguio City; Swimming for infants -- Philippines